Public Speaking Anxiety in Mechanical Engineering Students - Pipit Rahayu; Eripuddin Eripuddin; Devi Kurniawati; Alpino Susanto (STAI Hubbulwathan Duri, 2023)
This study explains students’ anxiety in public speaking at the second semester of the Mechanical Engineering Study Program. The purpose of this study was to describe the contributing factors that cause students to experience such condition. The participants in this study consisted of 22 students. This study used descriptive quantitative. The instruments used in the study were questionnaires. The questionnaire was the FCLAS (Foreign Language Classroom Anxiety Scale).The data were analyzed using a Likert scale to determine the factors that cause students' anxiety in public speaking. The results show that the factors that cause student anxiety in public speaking are internal factors and external factors. It shows the mean score of the level of students' anxiety , where the percentage of the two factors, namely internal factors, is 51% and external factors are 49% of the highest score of 100% points and the total number of questions was 33 numbers. Most correspondents are in the middle anxious classification with a median total of 3 points in both factors.